Automotive fuels and emissions - Hollembeak, Barry (Today's technician, 2005)
Theory, diagnostics, and service procedures for automotive fuel and emission systems are spotlighted in this newest Classroom and Shop Manual set to join the popular Today's Technician Series. Experienced author Barry Hollembeak enhances the reader's understanding of present-day automotive fuels and emission systems by covering the theories and procedures that underpin ASE high priority skills. The Classroom Manual builds upon facts and theories, while the Shop Manual, through performance-based objectives, helps readers acquire diagnostic and repair competency. Both manuals are tightly correlated with corresponding chapters and cross-references so that readers can make a sound connection between theoretical concepts and practical skills.